Management of children with auditory neuropathy spectrum disorder (ANSD) - Gökdogan,Çagil (2016)
ABSTRACT INTRODUCTION: ANSD is a challenging problem. OBJECTIVE: To present our experience on management of the children with ANSD with respect to clinical data. METHODS: This retrospective study included all children younger than 16 years of age who applied to the department between 2005 and 2013 (with the exception of newborn hearing screening NHS referrals). The data were derived from pure tone, OAEs and ABR tests, and further medical risk factors of the subjects were evaluated. RESULTS: ANSD was recognized in 74 ears of 40 children (B/U: 34/6) among 1952 children with SNHL (2.04%) detected among 9520 applicants to the department (0.42%). The clinical tests revealed that hearing loss greater than 15 dB was present in both ears of 38 cases. The degree of hearing loss was profound in 48% children, severe in 12% children, moderate in 28% children, mild in 10% children and normal in 5% children. ABRs were absent/abnormal in 37/3 ears and CMs were detected in all. Acoustic reflexes were absent in all ears. Rehabilitation was managed by CI and hearing aids in 15 and 23 cases, respectively. FM system was given to two cases displaying normal hearing but poor speech discrimination in noisy environments. CONCLUSION: ANSD is a relatively challenging problem for the audiology departments because of its various clinical features and difficulties in management. Our patients with ANSD most commonly displayed profound hearing loss. The number of overlooked cases may be minimized by performing ABR and OAE in every case referred with the suspicion of hearing loss.